Extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae in diabetic foot infections - Varaiya Ami; Dogra Jyotsana; Kulkarni Manasi; Bhalekar Pallavi (Wolters Kluwer Medknow Publications, 2008)
Aims: Diabetic foot lesions are a major medical, social, and economic problem and are the leading cause of hospitalization for patients with diabetes, worldwide. ESBL-producing bacteria may not be detectable by routine disc diffusion susceptibility test, leading to inappropriate use of antibiotics and treatment failure. There is not much information on ESBL-producing organisms causing diabetic foot infection. An attempt was therefore made to study the ESBL-producing Escherichia coli and Klebsiella pneumoniae in diabetic foot patients with type 2 diabetes mellitus. Materials and Methods: A total of 134 isolates of E. coli and K. pneumoniae were obtained from tissue, pus swab, and wound swab samples from diabetic foot ulcers submitted for routine microbiological analysis during the period January to December 2005 from patients with diabetic foot infections who had type 2 diabetes mellitus, attending S. L. Raheja Hospital. The above isolates were tested for antimicrobial susceptibility by disc diffusion technique according to clinical and laboratory standards institute (CLSI) guidelines. The screening for ESBL production was done by phenotypic confirmatory test using ceftazidime disc in the presence and absence of clavulanic acid as recommended by CLSI. Results: Among the 134 isolates, 54 (40.29%) were E. coli and 80 (59.70%) were K. pneumoniae; among which, ESBL production was detected in 31 (23.13%) isolates. Of these 31, 15 (48.38%) were E. coli and 16 (51.61%) were K. pneumoniae. All the ESBL-producing isolates were found to be 100% sensitive to carbapenem (imipenem and meropenem). Mortality was found to be 3.22%, the cause of death being septicemia leading to multiple organ failure. Conclusions: The prevalence of ESBLs among members of Enterobacteriaceae constitutes a serious threat to the current beta-lactam therapy, leading to treatment failure and consequent escalation of costs. There is an urgent need to emphasize rational use of drugs to minimize the misuse of available antimicrobials.